2019
DOI: 10.1016/j.joca.2019.02.795
|View full text |Cite
|
Sign up to set email alerts
|

Hip muscle strength and protection against structural worsening and poor function and disability outcomes in knee osteoarthritis

Abstract: Objective: Examine associations of hip abductor strength with (1) cartilage damage worsening in the tibiofemoral and patellofemoral compartments 2 years later, and (2) poor function and disability outcomes 5 years later. Methods: Participants had knee osteoarthritis (K/L ! 2) in at least one knee. Hip abductor strength was measured using Biodex Dynamometry. Participants underwent 3.0T MRI of both knees at baseline and 2 years later. Baseline-to-2-year cartilage damage progression, defined as any worsening of W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 60 publications
3
17
0
Order By: Relevance
“…13 A recent study from AH Chang also supported the finding that higher baseline hip abductor strength was associated with reduced risks of worsening medial patellofemoral and lateral tibiofemoral cartilage damage from baseline to two years, as well as poor function outcomes from baseline to five years. 18 Women with knee osteoarthritis were selected in this trial. Men and women with knee osteoarthritis employ different gait strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 A recent study from AH Chang also supported the finding that higher baseline hip abductor strength was associated with reduced risks of worsening medial patellofemoral and lateral tibiofemoral cartilage damage from baseline to two years, as well as poor function outcomes from baseline to five years. 18 Women with knee osteoarthritis were selected in this trial. Men and women with knee osteoarthritis employ different gait strategies.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Recent discoveries have supported a beneficial role of the hip abductor as a potential therapeutic target in managing knee osteoarthritis. 18 Compared with the quadriceps, research on hip abductor muscle is limited. Only a few of these studies were rated as high quality according to a recent meta-analysis.…”
mentioning
confidence: 99%
“…However, in the current chosen primary analysis, in compliance with our selection criteria and current power constraint, we decided to adjust for KOOS-pain and psychosocial difficulties. BMI was not included in the model because the strength results were normalized to body weight(91), BMI showed no discrimination in the prior study(1), and it showed moderate-high correlation with all candidate strength predictors in the current correlation matrix (e-appendix).Figure 1shows the diagram of the causal modeling of the total effect of strength on (…”
mentioning
confidence: 99%
“…Vasilevska et al and Grimaldi et al described GTPS and the iliotibial band 32,183) . Furthermore, the strength involving the hip abductors improved the prognosis of knee osteoarthritis 184) , and thus some part of knee osteoarthritis possibly attributed to GMedS.…”
Section: Reportmentioning
confidence: 96%